Community-level spillover effects of an intervention to prevent intimate partner violence and HIV transmission in rural Ethiopia - Leight, Jessica; Deyessa, Negussie; Verani, Fabio; Tewolde, Samuel; Sharma, Vandana (BMJ, 2021)
Background: Intimate partner violence (IPV) is associated with adverse health and psychosocial outcomes. We analysed the spillover effects of Unite for a Better Life (UBL), an intervention evaluated in a cluster randomised controlled trial using a double-randomised design; previous evidence suggests UBL reduced IPV in rural Ethiopia among direct beneficiaries. Methods: Villages (n=64) were randomly allocated to control, or to receive UBL delivered to men, women or couples. Each cluster comprised 106 surveyed households, including 21 randomly selected indirect beneficiary households who were not included in the intervention. Primary and secondary IPV outcomes included women’s experience and men’s perpetration of past-year physical or sexual IPV 24 months postintervention. An intention-to-treat analysis was conducted comparing indirect beneficiaries to sampled households in control communities. The analysis includes 2516 households surveyed at baseline in 2014–2015 (1680 households in the control arm, 258 indirect beneficiary households in the couples’ arm, 287 indirect beneficiary households in the women’s arm and 291 indirect beneficiary households in the men’s arm). Follow-up data were available from 88% of baseline respondents and 86% of baseline spouses surveyed in 2017–2018, a total of 4379 individuals. Results: Among indirect beneficiaries, there was no statistically significant intervention effect on women’s past-year experience of physical or sexual IPV, while men’s UBL significantly reduced reported perpetration of past-year sexual IPV (Adjusted Odds Ratio: 0.55; 95% CI 0.38 to 0.80, p=0.002). The intervention effects among indirect beneficiaries were statistically similar to those reported for the direct beneficiaries. In general, the hypothesis of equal effects cannot be rejected. Conclusion: A gender-transformative intervention delivered to men was effective in reducing reported IPV even among indirect beneficiaries, suggesting that the programme had positive spillover effects in diffusing information and changing behaviours within the broader community.